Juridical Aspects of Divorce Disputes and Marriage Cancellations on the Legal Status of Children - Salmah Salmah (IHSA Institute, 2022)
This study aims to find out the process of enactment of the procedural law of the religious court to resolve the divorce conflict and marriage annulment and to find out the form of marital dispute resolution that is related to the status of children in divorce disputes and marriage annulments. The method used in this study is a qualitative method, with a normative juridical approach as the main approach and an empirical juridical approach as a supporting approach. Sources of data in this study obtained from secondary data as the main data and primary as supporting data. Furthermore, the data is then processed by means of qualitative methods. The results of this study are the law guarantees the status of children born from an annulled marriage will not have an impact on the child as a victim of a court decision due to the cancellation of his parents' marriage and 2. According to law, divorce can only occur if there is a legally valid marriage while the decision to cancel Marriage which has permanent legal force has legal consequences to return to its original position before the marriage or marriage is considered to have never existed.